Can Ultrasound-Guided Femoral Vein Measurements Predict Spinal Anesthesia-Induced Hypotension in Non-Obstetric Surgery? A Prospective Observational Study - Ayşe Yılmaz; Ufuk Demir; Öztürk Taşkın; Veysel Garani Soylu; Zahide Doğanay (MDPI AG, 2022)
Background and objectives: To investigate whether ultrasound (US)-guided femoral vein (FV) and inferior vena cava (IVC) measurements obtained before spinal anesthesia (SA) can be utilized to predict SA-induced hypotension (SAIH) and to identify risk factors associated with SAIH in patients undergoing non-obstetric surgery under SA. Methods: This was a prospective observational study conducted between November 2021 and April 2022. The study included 95 patients over the age of 18 with an American Society of Anesthesiologists (ASA) physical status score of 1 or 2. The maximum and minimum diameters of FV and IVC were measured under US guidance before SA initiation, and the collapsibility index values of FV and IVC were calculated. Patients with and without SAIH were compared. Results: SAIH was observed in 12 patients (12.6%). Patients with and without SAIH were similar in terms of age [58 (IQR: 19–70) vs. 48 (IQR: 21–71; p = 0.081) and sex (males comprised 63.9% of the SAIH and 75.0% of the non-SAIH groups) (p = 0.533). According to univariate analysis, no significant relationship was found between SAIH and any of the FV or IVC measurements. Multiple logistic regression analysis revealed that having an ASA class of 2 was the only independent risk factor for SAIH development (p = 0.014), after adjusting for age, sex, and all other relevant parameters. Conclusions: There is not enough evidence to accept the feasibility of utilizing US-guided FV or IVC measurements to screen for SAIH development in patients undergoing non-obstetric surgery under SA. For this, multicenter studies with more participants are needed.
Keywords: Male; Adult; Medicine (General); spinal anesthesia-induced hypotension; femoral vein diameter; femoral vein collapsibility index; non-obstetric surgery; Middle Aged; Hypotension, Controlled; Femoral Vein; Anesthesia, Spinal; Article; R5-920; non-obstetric surgery; Humans; femoral vein collapsibility index; Female; femoral vein diameter; Ultrasonography, Interventional; spinal anesthesia-induced hypotension; Ultrasonography